Exploring the Depths of Qualitative Research in Services - Jain, Atishay (Journal of Advanced Research in Service Management, 2023)
Qualitative research in services has evolved into a vital and adaptable approach for comprehending the intricacies of the service industry. This comprehensive review explores its historical development, methodologies, strengths, and limitations, underscoring its significance in gaining holistic insights into diverse service sectors. Tracing its roots back to the mid-20th century, qualitative research in services has matured through the pioneering work of scholars like Robert K. Yin and Barney G. Glaser. It encompasses an array of methodologies, including interviews, focus groups, participant observation, content analysis, and case studies, each tailored to delve into specific aspects of service provision and consumption. The strengths of qualitative research in services lie in its capacity to provide rich, contextually relevant data, contribute to theory development, offer flexibility in research design, and consider the perspectives of multiple stakeholders. However, it is not without limitations, including potential subjectivity, resource intensity, challenges in data management, and ethical considerations. Recent trends reflect the ever-changing service landscape, with digital ethnography, customer journey mapping, service design thinking, mixed-methods approaches, and a focus on sustainability and ethical consumption emerging as prominent themes. In conclusion, qualitative research in services remains indispensable for unraveling the complexities of the service sector, offering a profound understanding of service experiences, organizational practices, and customer interactions. Its adaptability and enduring relevance ensure its continued contribution to innovation and improved service quality in an evolving world.